Identity Negotiation and Marginalization: The Struggle for Cultural Assimilation of a Chinese-American Teenager in the Short Film “Americanized” (2021) - Pratama, Rifka; Wulandari, Retno (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2024)
As a minority group in the United States, Chinese-Americans encounter a multitude of challenges throughout the process of integrating into the dominant societal structure. For Chinese-American adolescents, these challenges are particularly intricate, given that they are in a phase of self-discovery and face psychological issues related to maturity and existence. The short film “Americanized” (2021) portrays the phenomenon of identity negotiation experienced by the fifth generation of Chinese-Americans attempting to assimilate into both the African-American and Asian-American communities. However, due to a perceived lack of alignment with the cultural and normative expectations of both groups, the character ultimately becomes marginalized. Her efforts to negotiate her identity are evident in her use of linguistic styles, fashion, gestures, and elements of hip-hop culture that symbolize her identity, yet ultimately result in further alienation from both groups. This phenomenon illustrates the challenges Asian- American adolescents face in attempting to find a place between the two cultures, and underscores the complexity of the assimilation process that can result in identity marginalization.